Analisis Kualitas Daya Listrik Di Gedung A Fakultas Sains Dan Teknologi Universitas Jambi - Nanda Dwi Septiawan; Abdul Manab; Andre Rabiula; Dasrinal Tessal (Universitas Katolik Widya Karya Malang, 2024)
A reliable, efficient and high quality electrical energy supply is certainly very necessary. Frequent damage to electronic equipment and practical equipment in Building A, Faculty of Science and Technology (FST), Jambi University, prompted the author to conduct research on analyzing the quality of electrical power in this building. The research aims to analyze the quality of electrical power in building A FST. The research method used is the observation method which cannot influence the variables studied but can only record and observe the data that has been measured. The power quality quantities measured are voltage, current, active power, reactive power, power factor, voltage harmonics and current harmonics in each main panel. Based on the research results, the problem that occurs in the main panel of transformer A is load imbalance, namely at a percentage of 5.56% to 6%, the standard set by the IEC is only 5%. and the occurrence of current harmonic distortion (THDi) at a percentage of between 24%, the standard set by IEEE is 12%. The problem that occurs in the main panel of transformer B is that it has a low power factor value in the R and T phases, namely below 0.85. The occurrence of load imbalance is at a percentage of 10.9% to 12%, the standard set by the IEC is only 5%. The occurrence of voltage fluctuations is +7.4%, the standard according to PUIL 2011 is +5% with a value of 231 Volts and -10% with a value of 198 Volts and the occurrence of current harmonic distortion (THDi) is very high at a percentage of 29.83% to 58.419%, the value permitted by the IEEE standard is 15%.